Copper‐Catalyzed Triboration of Terminal Alkynes Using B(2)pin(2): Efficient Synthesis of 1,1,2‐Triborylalkenes - Liu, Xiaocui (Angew Chem Int Ed Engl, 2019)
We report herein the catalytic triboration of terminal alkynes with B(2)pin(2) (bis(pinacolato)diboron) using readily available Cu(OAc)(2) and P(n)Bu(3). Various 1,1,2‐triborylalkenes, a class of compounds that have been demonstrated to be potential matrix metalloproteinase (MMP‐2) inhibitors, were obtained directly in moderate to good yields. The process features mild reaction conditions, a broad substrate scope, and good functional group tolerance. This copper‐catalyzed reaction can be conducted on a gram scale to produce the corresponding 1,1,2‐triborylalkenes in modest yields. The utility of these products was demonstrated by further transformations of the C−B bonds to prepare gem‐dihaloborylalkenes (F, Cl, Br), monohaloborylalkenes (Cl, Br), and trans‐diaryldiborylalkenes, which serve as important synthons and have previously been challenging to prepare.